2011
DOI: 10.4172/2155-6156.1000131
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Calcium Channel Blocker “Nifedipine” on Abnormalities of Platelets and Lipid Metabolism in Patients with Type II Diabetes Mellitus

Abstract: Background and Aim: Platelets play a role in the microvascular as well as macrovascular complications of diabetic patients with serious implications in the pathogenesis of vascular disease in patients with type 2 diabetes. Hyperglycemia changes platelet functions by impairing calcium homeostasis. So, it is important to study the effect of nifedipine on platelet functions and cardiovascular complications associated with diabetes. Methods: There were 3 groups, i.e. healthy non diabetics (control), type 2 diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In a study performed to investigate the beneficial effects of nifedipine on abnormalities of platelets and lipid metabolism in patients with type II diabetes mellitus, it was found nifedipine produced significant reduction of lipid profiles except for HDL which showed significant increase 15 . This result agrees with our findings which demonstrated that nifedipine produced highly significant reduction in LDL-cholesterol blood level in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed to investigate the beneficial effects of nifedipine on abnormalities of platelets and lipid metabolism in patients with type II diabetes mellitus, it was found nifedipine produced significant reduction of lipid profiles except for HDL which showed significant increase 15 . This result agrees with our findings which demonstrated that nifedipine produced highly significant reduction in LDL-cholesterol blood level in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In severe tuberculosis, endocrine function of Pancreas has also been found to be adversely affected. In patients with concomitant diabetes and tuberculosis, a higher incidence of chronic calcific pancreatitis occurs, leading to an absolute or relative insulin deficiency state [80]. Dysregulation of energy homeostasis in the TB disease may cause by a family of fattyacid-transporter proteins in the tubercle bacillus.…”
Section: Causes Of Glucose Intolerance In Tuberculosismentioning
confidence: 99%
“…Hyperglycemia-derived oxygen free radicals are also considered mediators of diabetic complications [37]. Hyperglycemia changes platelet function [38] by impairing calcium homeostasis and thereby alters aspects of platelet activation and aggregation, including platelet conformation and release of mediators. Diabetes is much more complicated than hyperglycemia and is associated with several risk factors.…”
Section: Alterations In Glucose Levelsmentioning
confidence: 99%